Lending of first versus lending of last resort: The Bulgarian financial crisis of 1996/1997 - Michael Berlemann; Nikolay Nenovsky (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2003)
In 1996/1997 Bulgaria was hit by a severe financial crisis, spreading from a banking crisis to a currency crisis. However, in comparison to the Asian, the Russian or the recent Tango Crisis the Bulgarian Crisis did arouse relatively low international interest. We argue that the Bulgarian Financial Crisis might serve as an illustrative example of a twin crisis involving both a currency and a banking crisis. While the Bulgarian Crisis had some properties of so-called fundamental crises, as explained by first generation models of currency crises, the severity of the crisis was primarily due to systematic moral hazard behaviour of the banking sector. Special attention is paid to the crucial role the Bulgarian National Bank played in the pre-crisis and during the crisis period when acting more as a lender of first than a lender of last resort. We also show how Bulgaria managed to overcome the crisis by introducing a second generation currency board allowing the central bank to act as a strictly limited lender of last resort thereby making the country less prone to a financial crisis in the future.
Keywords: E42; E5; F02; P34; 330; Lender of Last Resort; Financial Crises; Twin Crises; Currency Boards; Bulgaria; Bankenkrise; Moral Hazard; Currency Board; Bulgarien; Finanzmarktkrise; Lender of Last Resort